DEVELOPMENT OF PROPORTION MATERIAL MATHEMATICS MODULE FOR CLASS VII SMP / MTs STUDENTS BASED ON CURRICULUM 2013 - Hari Fatkhul Humam; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2019)
Limited teaching material is one of the problems that affect the achievement of learning goals. Teaching materials that can help students learn independently are modules. This study is a development study to produce mathematics teaching materials on comparison for class VII students of Junior High School (SMP / MTs) based on the 2013 curriculum and determine the quality of the developed modules suitable for mathematics learning. This study uses the developed Research and Development (R & D) model, including identifying potential and problems, gathering information, designing products, validating product designs, revising product design, product testing stages, and product revisions. The subject of this module's study and development are material experts, media experts, and students. The 2013 curriculum-based mathematics module is developed based on five main learning experiences: observing, asking questions, gathering information, associating, and communicating. The study results indicate that the mathematics teaching material for comparisons for class VII students of SMP / MTs based on the 2013 curriculum has good quality. Based on the assessment by material experts obtained an average score of 116.67 that meets the criteria of good, by media experts received an average score of 112.33, which meets the requirements of interest, and the results of student responses to the module indicate that the quality of the module good With an average score of 116.5. Based on the study results, the mathematics module of comparison material based on the 2013 curriculum is appropriate for mathematics learning.